Analyzing Performance Determinants: Islamic Rural Bank Performance in Indonesia - Baroroh, Hilmy (Journal of Islamic Economics and Social Science (JIESS), 2023)
Islamic Rural Banks are unique in terms of financing distribution because they are limited to the scope of certain areas in Indonesia. This study examines internal and external factors on the performance of Islamic Rural Banks in Indonesia which present financial products, especially for the micro, small and medium business sectors. ROA measures performance variables, internal variables consist of NPF, FDR, CAR, and PLS, external variables consist of economic growth, inflation, and the BI rate. The data comes from the IRBs Statistical Annual Report for 2015-2021 using the Auto Regressive Distributed Lag (ARDL) analysis method to see long-term and short-term relationships between variables. This study found that two internal variables, namely FDR and PLS, experienced delays but had an effect on ROA in the short term, for NPF and CAR in the short-term research had no effect on ROA. As for external variables, only the BI rate affects ROA, while GDP and inflation do not affect ROA. Furthermore, the results of long-term research show that all internal factors affect ROA, while external factors, only the BI rate, affect ROA. From the results of this study, it was found that IRBS should focus on managing their business rather than expanding the scope of business because the revenue that IRBS gets comes from their performance which tends to be influenced by internal IRBS factors.